Germany : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 1998)
This Selected Issues paper and Statistical Appendix analyzes Germany's past fiscal policy behavior and assesses the likely adjustments that would be necessary to bring future fiscal policy behavior in line with European Monetary Union and the Stability and Growth Pact requirements. Using estimated fiscal policy reaction functions that take account Germany's decentralized fiscal decision-making structure, the statistical results suggest that discretionary fiscal policy at the general government level has maintained a procyclical stance since the end of the 1970s. The paper also examines disaggregated labor market developments in Germany.